2017
DOI: 10.1016/j.ibmb.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Orcokinin neuropeptides regulate ecdysis in the hemimetabolous insect Rhodnius prolixus

Abstract: To grow and develop insects must undergo ecdysis. During this process, the individual sheds the old cuticle to emerge as the following developmental stage. During ecdysis, different programed behaviors are regulated by neuropeptidergic pathways. In general, components of these pathways are better characterized in crustacean and holometabolous insects than in hemimetabola. In insects, the orkoninin gene produces two different neuropeptide precursors by alternative splicing: orcokinin A and orcokinin B. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
4
27

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 32 publications
0
48
4
27
Order By: Relevance
“…Several orthogroups contain potentially novel genes that show no homology outside the Hemiptera and await direct experimental analysis, for which the Hemiptera are particularly amenable ( e.g. , [49-52, reviewed in 5]). Secondly, there are hemipteran-specific orthogroups of proteins with recognized functional domains and homologs in other insects, but where evolutionary divergence has led to lineage-specific subfamilies.…”
Section: Resultsmentioning
confidence: 99%
“…Several orthogroups contain potentially novel genes that show no homology outside the Hemiptera and await direct experimental analysis, for which the Hemiptera are particularly amenable ( e.g. , [49-52, reviewed in 5]). Secondly, there are hemipteran-specific orthogroups of proteins with recognized functional domains and homologs in other insects, but where evolutionary divergence has led to lineage-specific subfamilies.…”
Section: Resultsmentioning
confidence: 99%
“…The anatomical distribution and pharmacological actions of PP/OK‐type neuropeptides have been characterized in protostomian invertebrates, including mollusks and arthropods (Beck et al, ; De Lange, van Golen, & van Minnen, ; Dircksen et al, ; Hall & Lloyd, ; Jiang et al, ; Lloyd et al, ; Pearson & Lloyd, ; Wulff et al, ). Here we report the first detailed anatomical analysis of PP/OK‐type neuropeptide expression in a deuterostomian invertebrate, the starfish A. rubens .…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical distribution and pharmacological actions of PP/OKtype neuropeptides have been characterized in protostomian invertebrates, including mollusks and arthropods (Beck et al, 2000;De Lange, van Golen, & van Minnen, 1997;Dircksen et al, 2000;Hall & Lloyd, 1990;Jiang et al, 2015;Lloyd et al, 1996;Pearson & Lloyd, 1989;Wulff et al, 2017). 1950).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies have revealed that OKs also alter the rhythmic motor output of the stomatogastric nervous system in crustaceans (Li et al, 2002;Skiebe, Dreger, Meseke, Evers, & Hucho, 2002). Furthermore, experimental studies on insects have revealed that OKs cause a phase-dependent shift in circadian locomotor activity in cockroaches (Hofer & Homberg, 2006), regulate "awakening" behavior in the beetle Tribolium castaneum (Jiang, Kim, & Park, 2015) and regulate ecdysis in the kissing bug Rhodnius prolixus (Wulff et al, 2017). Thus, PP/OK-type neuropeptides have a variety of actions in mollusks and arthropods but with stimulatory actions appearing to be a common theme.…”
mentioning
confidence: 99%